Testiranje gibljivosti košarkarjev z modificirano FMS-metodo - Sirnik, Matic (Šport (Ljubljana), 2023)
In today‘s professional sport, including basketball, mobility is an important skill, which in connection with other movement skills allows athletes to have better mobility efficiency, an optimal movement technique, psycho-physical relaxation and are less sus- ceptible to injuries. By demonstrating the use of the modified FMS test system, we want to improve the level of mobility testing which undoubtedly is an important movement skill for basketball players. We strive to improve the mobility training, in order to eliminate the consequences of improper body posture and overload syndromes, consequently creating better conditions for training the movement technique.
Keywords: dodatni testi; gibalne sposobnosti; gibljivost; košarka; šport; testni sistem FMS